The Influence of Talent management on Employee Performance Mediated by Employee Engagement and Job Satisfaction at BUMN Banking in Batam - Alden Nelson; Wikandriya Pradinang (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to determine the relationship between talent management and employee performance through the role of employee involvement and job satisfaction as mediation. This research uses a quantitative method with a purposive sampling technique by distributing questionnaires to respondents. The data used were 400 BUMN Bank employee respondents in Batam. The Smart PLS 3 program is an application used to test research data. The results of the research explain that employee involvement influences employee performance, job satisfaction influences employee performance, talent management influences employee engagement, talent management influences job satisfaction, talent management influences employee performance mediated by employee involvement and talent management influences employee performance. mediated job satisfaction.